Hepatitis-B surface antigen and cirrhosis in Iraq. Issue 2 (February 1976) - Boxall, E H; Flewett, T H; Paton, A; Rassam, S W
Abstract : Hepatitis-B surface antigen was found in 58% of 64 patients with cirrhosis in Iraq using counter immunoelectrophoresis (CIE), radioimmunoassay (RIA), and three commercial haemagglutination tests–Auscell (Abbott Laboratories), Hepatest (Wellcome Reagents Ltd.), and Hepanosticon (Organon Teknika). CIE detected about half as many positives as the other methods; RIA was the most sensitive. The number of positive reactions was much higher than in any previously reported series of patients with cirrhosis and seven times higher than in a normal hospital control population.